Diversity and Distribution of Hydropsychidae (Insecta: Trichoptera) in Hala-Bala Wildlife Sanctuary, Narathiwat Province - Rajsuwan, Pattamaporn; Thawarorit, Kitiya; Puwaphut, Rugchanok (Princess of Naradhiwas University Journal, 2021)
Diversity and distributions of Hydropsychidae caddisflies were investigated at 4 headwater streams of Sirindhorn, Sairung, Sritaksin and Bale Waterfalls in Hala-Bala Wildlife Sanctuary, Narathiwat Province. Field samplings were conducted during June to September 2019 and February to May 2020. Samples of the larvae were collected using hand picking and a D-frame net (mesh 425 µm) whereas those of the adults were collected using an ultraviolet light trap. Some physico-chemical parameters of water quality were also measured using field water quality equipment. Eight thousand, nine hundred and twenty of larval individuals were found included three subfamilies and nine genera. Results of this study showed that Macronematinae was the most diverse (5 genera) included Macrostemum, Oestropsyche, Pseudoleptonema, Trichomacronema and Polymorphanisus followed by Hydropsychinae (3 genera) included Cheumatopsyche, Hydropsyche, Hydromanicus and Diplectroninae was only found Diplectrona, respectively. Cheumatopsyche was the most abundant with 6,235 individuals (69.90%). Cheumatopsyche, Hydropsyche and Diplectrona were both dominant and widespread taxa and found at all sites of collection and almost every month of collection. However, narrow distribution and a few of individuals of Pseudoleptonema was found and recorded only in Sirindhorn Waterfall. Two thousand, three hundred and thirty-nine adult individuals were found included 3 subfamilies, 6 genera and 28 species. In adults, Hydropsychinae showed high diversity with 21 species followed by Macronematinae (5 species) and Diplectroninae (2 species), respectively. Cheumatopsyche copia was dominant, widespread and high abundant which is in accordance with the result of larvae. Macrostemum midas was also dominant species in Sirindhorn, Sairung and Bale Waterfalls.